Effect of Training Program on Snack Consumption in Elementary School Girls: Application of the BASNEF Model - Zahra Jalili; Zahra Saboohi; Reza Tavakoli (Hamadan University of Medical Sciences, 2021)
Aims: Many non-communicable diseases such as diabetes, osteoporosis, and high blood pressure are related to unhealthy eating habits and patterns formed in childhood and the teenage period. This study investigated the effect of a training program based on the BASNEF model on snack consumption in elementary school girls in the second period. Materials & Methods: This quasi-experimental study was conducted on 200 elementary school girls in Saveh, Iran, in 2019. Samples were selected by random sampling method and randomly assigned into two experimental and control groups (100 people in each group). The data collection tool was a researcher-made questionnaire, including demographic characteristics, BASNEF model constructs that were completed before, and 3 months after the experimental and control groups' educational intervention. The training program was performed in 3 sessions of education for students, one session for parents, and one session for principals, deputies, teachers, and school buffet officials. Data were analyzed by SPSS 24 software using Chi-square, paired, and independent t-tests. Findings: Results showed that before the intervention, there was no significant difference between the experimental and control groups in terms of attitude, enabling factors, subjective norms, intention, and snack consumption behaviors (p>0.05). After the intervention, the mean score of attitude, subjective norms, enabling factors, intention, and healthy and unhealthy snack consumption behaviors in the experimental group were significantly higher than the control group (p<0.001). Conclusion: Educational intervention based on the BASNEF model has effectively increased the consumption of healthy snacks and reduced the consumption of unhealthy snacks in elementary school girls.